Multiallelic Rare Variants in BBS Genes Support an Oligogenic Ciliopathy in a Non-obese Juvenile-Onset Syndromic Diabetic Patient: A Case Report - Dallali, Hamza; Kheriji, Nadia; Kammoun, Wafa; Mrad, Mehdi; Soltani, Manel; Trabelsi, Hajer; Hamdi, Walid; Bahlous, Afef; Ben Ahmed, Melika; Mahjoub, Faten; Jamoussi, Henda; Abdelhak, Sonia; et al. (Frontiers in Genetics, 2021)
Juvenile Onset Diabetes may occur in the context of a rare syndromic presentation suggesting a monogenic etiology rather than a common multifactorial diabetes. In the present study, we report the case of a young diabetic Tunisian patient presenting learning problems, speech deficits, short stature, brachydactyly and a normal weight. Whole exome sequencing analysis revealed five rare genetic variants in genes involved in the regulation of clium biogenesis and function: BBS1, BBS4, TTC8, MKS1 and CEP290. We analyzed variants combinations pathogenicity using the recently developed ORVAL tool, and we hypothesized that cumulative synergetic effects of the five variants could explain the phenotype observed in our patient. Therefore, our investigation suggested a genetic diagnosis of Bardet-Biedl syndrome with an oligenic inheritance pattern rather than a monogenic diabetes. Although there is no curative therapy for this ciliopathy at the moment, a genetic diagnosis may offer other supportive care options, including the prevention of other possible clinical manifestations of this syndrome, mainly renal abnormalities, obesity, liver fibrosis and hypertension, as well as the genetic counseling for family members.